A history of the colonization of Africa by alien races - Johnston, Harry, 1858-1927 (Salt Lake City, UT : Project Gutenberg, 2025)
"A history of the colonization of Africa by alien races" by Harry Johnston is a historical account written in the early 20th century. The work traces the major waves of foreign intervention and settlement in Africa, focusing specifically on the movements and influences of non-indigenous peoples rather than internal African developments. The central topic is the complex process of colonization$1 (Bby Asians, Europeans, and other outside groups$1 (Bacross Africa from prehistoric times up to the author's present era. The opening of the book begins with a detailed exploration of humanity's early migrations into Africa, examining the origins and differentiations of the continent$1 (Bs major population groups such as the Bushmen, various Negro types, and negroid or mixed peoples like the Fula and Hausa. Johnston discusses anthropological and linguistic evidence to address questions about where these groups came from, how they dispersed, and how they interacted with both earlier and later arrivals (including possible prehistoric Caucasian populations). He describes the impact of environmental factors, interactions with other species, and a succession of external human waves$1 (Bfrom ancient Near Eastern populations to Malays in Madagascar. After establishing these ancient and pre-colonial foundations, the narrative shifts towards the earliest historical colonizers, notably the Phoenicians, setting up the chronological march through Africa$1 (Bs encounters with successive alien races. (This is an automatically generated summary.)s
Release date is 2025-04-16
Peter Becker, KD Weeks and the Online Distributed Proofreading Team at https://www.pgdp.net (This file was produced from images generously made available by The Internet Archive)
Keywords: Africa -- Discovery and exploration; Africa -- Colonization